Taking Care of the Weak and the Oppressed: Stories of the Transgenders Rediscovering Islam - Lina Amiliya; M. Lathiful Khuluq (Yinyang: Jurnal Studi Islam Gender dan Anak, 2025)
The existence of a minor response given by the major community makes waria or transgender increasingly oppressed and marginalized. In addition, the injustice that applies in community law makes it difficult for waria to access various public facilities, one of which is religious. So that the space for the expression of his spirituality in the public sphere is limited. The purpose of this research is to find out the life story of transgender people in the Waria Al-Fatah Islamic Boarding School, Yogyakarta, who became a weak and oppressed minority group and were then able to reinvent Islam. The method used is a qualitative-descriptive research. The data were analyzed using the theory of symbolic interactionism. This qualitative-descriptive study uses a case study approach. Data were collected through interviews with the five transgender students, observation, and document analysis. Data were processed using Miles and Huberman’s model and analyzed with symbolic interactionism theory. The results of the study show that the establishment of the Yogyakarta Al-Fatah Waria Islamic Boarding School is able to become a place that provides a safe space for transgender people to study and re-find their religion, namely Islam, in the midst of threats and discrimination that befell them in public spaces. Transgender people are given the freedom and flexibility to express their spirituality according to their individual convenience. In addition, it requires the role and ongoing support of several parties so that this Islamic boarding school continues to exist in the midst of public views that override the humanitarian side. This also includes the role of support as a mediator in resolving and maintaining transgender people in this Islamic Boarding School.